Grit: the good, the bad and the ugly. Issue 5 (20th November 2020) - Arli, Denni; Tjiptono, Fandy; Tkaczynski, Aaron; Bakpayev, Marat
Abstract : Purpose: The concept of grit has been receiving increased attention in recent years. Grit is a trait that enables individuals to persevere while facing challenges and obstacles in life, sometimes "winning at any cost". The purpose of the study is to understand how ethical views may vary among different groups of people segmented on grittiness. Our key argument is that grittier segment is more inclined towards Machiavellian factors (amorality, desire for control, desire for status, distrust of others) and materialism. Design/methodology/approach: Data derived from self-administered questionnaires completed by convenience samples of Indonesians living in Daerah Istimewa Yogyakarta (DIY), a region commonly considered as the miniature of Indonesia. Turning to market segmentation tools ( n  = 467), we first segment people based on their level of grittiness and, subsequently, investigate each segment's perception towards various Machiavellian factors (amorality, desire for control, distrust of others) and materialistic attitudes. Findings: The study identified three segments of grittiness: The Least Gritty (the Good), The More Gritty (the Bad) and The Most Gritty (the Ugly). The results of this study showed the dark side of grit. Individuals with higher grit traits are more likely to behave unethically which could be referred to as "bad" and "ugly". To help them succeed, cheating and lying are more likely considered acceptable by gritty individuals compared to less gritty "good" individuals. Practical implications: Merely focussing on grit–be it grit promotion or training–may produce individuals who achieve success at all costs and disregard ethical values. An implication from the study is not to discourage developing grit in individuals but instead to add and emphasise ethical components. This implication is especially critical for educators and managers developing grit as a part of their activities. Originality/value: The results of this study will have important theoretical implications and managerial implications educators balancing the consequences of teaching grit, but also for managers interested in understanding employees' level of grit within their workplaces along with ethical considerations.